2015
DOI: 10.1093/conphys/cov008
|View full text |Cite
|
Sign up to set email alerts
|

The influence of time in captivity, food intake and acute trauma on blood analytes of juvenile Steller sea lions,Eumetopias jubatus

Abstract: We identified five blood parameters associated with physiological changes experienced by wild juvenile Steller sea lions while held in temporary captivity. These key parameters could offer a way to better characterize the health status of juvenile Steller sea lion populations in the wild.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Subsequently, two tags per animal were used to increase and estimate data return probability. For initial deployments animals were held in extended captivity up to eight weeks after surgery prior to release to allow comprehensive assessments of postoperative effects including physiological changes [56][57][58][59], stress response [60], as well as behavioral indicators of pain [61,62]. Following release, all animals were tracked via externally attached satellite telemetry transmitters for periods ranging from one week to four months [57,63].…”
Section: Life-long Implanted Vital Rate Transmittersmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, two tags per animal were used to increase and estimate data return probability. For initial deployments animals were held in extended captivity up to eight weeks after surgery prior to release to allow comprehensive assessments of postoperative effects including physiological changes [56][57][58][59], stress response [60], as well as behavioral indicators of pain [61,62]. Following release, all animals were tracked via externally attached satellite telemetry transmitters for periods ranging from one week to four months [57,63].…”
Section: Life-long Implanted Vital Rate Transmittersmentioning
confidence: 99%
“…healed upon external, visual examination and palpation, and the initial postoperative elevation of blood analytes associated with the inflammatory response had returned to pre-surgical levels after five weeks [43,57,59]. From these observations, the authors derived a 45-day postoperative survival study inclusion criterion.…”
Section: Life-long Implanted Vital Rate Transmittersmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological responses from stressful events are commonly used as indicators of health and survival and can be tracked by changes in glucocorticoids and haptoglobins in the blood ( Thomton and Mellish, 2007 ; Franceschini et al , 2008 ; Petrauskas et al , 2008 ; Bechshøft et al , 2013 ). Skinner et al (2015) recently identified six principal analytes as important indicators of physiological responses to various research activities specific to this group of sea lions. Several commonly measured blood parameters, including serum globulins (GLOB; in grams per decilitre), glucose (GLU; in milligrams per decilitre), total bilirubin (TBIL; in milligrams per decilitre), platelets (PLT; ×10 3 per millimetre cubed), red blood cells (RBC; ×10 6 per millimetre cubed) and leucocytes (WBC; ×10 3 per millimetre cubed), fluctuated in response to food intake, time in captivity and recovery from LHX-1 implantation ( Mellish et al , 2006 ; Skinner et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“… Skinner et al (2015) recently identified six principal analytes as important indicators of physiological responses to various research activities specific to this group of sea lions. Several commonly measured blood parameters, including serum globulins (GLOB; in grams per decilitre), glucose (GLU; in milligrams per decilitre), total bilirubin (TBIL; in milligrams per decilitre), platelets (PLT; ×10 3 per millimetre cubed), red blood cells (RBC; ×10 6 per millimetre cubed) and leucocytes (WBC; ×10 3 per millimetre cubed), fluctuated in response to food intake, time in captivity and recovery from LHX-1 implantation ( Mellish et al , 2006 ; Skinner et al , 2015 ). While a single-point measure would not be likely to have the ability to predict long-term survival, the time required for an individual to return baseline blood parameters after a perturbation event is a useful metric, as suggested by its common use in rehabilitation cases ( Greig et al , 2010 ; Witte et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%